Orthodontic treatment of a patient with special needs: a case report - Alexa Nicole Guerrero Aizpurúa; Simone Gomes de Oliveira; Antonio Carlos Pereira; Flávio Henrique Baggio Aguiar; Márcio Zaffalon Casati; Eduardo César Almada Santos (Faculdade São Leopoldo Mandic, 2024)
ABSTRACT This report presents the case of an adult patient with mental and intellectual limitations, whose main complaint was dental aesthetics. Dental treatment was performed at the Piracicaba Dental School and approved by the Ethics Committee (CAAE: 65752322.2.0000.5418). Clinically, the patient had inadequacies in the dental arrangement, with periodontal involvement that put the dental elements at risk. In intraoral clinical aspects, the deficiency was identified as maxillary atresia. The buccolingual inclination of the mandibular anterior teeth highlighted the severe crowding and anterior crossing of these teeth. Dental treatment was carried out aiming at the remission of periodontal and orthodontic problems in an integrated manner and with approaches that allowed greater interaction, participation, and patient compliance during treatment. Supra and subgingival scrapings and extraction of the upper left lateral incisor were performed. After three months of periodontal treatment, orthodontic treatment was started with fixed orthodontic appliances. The main objective was to level and align the teeth in both arches to achieve better aesthetic and functional conditions. Due to the COVID-19 pandemic, treatment has been discontinued. This resulted in the regression of the results obtained, including regarding self-care. People with disabilities require dental care with specific strategies for their needs, which must be carried out by a multidisciplinary team. Despite the access limitation imposed by the pandemic, the patient reestablished his motivation to restart treatment, which was facilitated by the bond of trust established between him and the team.